Prevalence of dental caries and oral hygiene practices among elderly people: a descriptive cross-sectional study from Nepal - Yadav, Sunny K.; Bist, Amrit (International Journal Of Community Medicine And Public Health, 2023)
Background: Dental caries is one of the most prevalent oral diseases of public health concern affecting elder people. The main reasons for caries arise in elderly people are increase in sugar consumption, poor oral hygiene, microbial plaque, periodontal disease, dietary habits, low socioeconomic status and infrequent dental visits. The oral hygiene is essential to general health and quality of life. Methods: A descriptive cross-sectional study was conducted among 246 elder people. Systematic random sampling was used for data collection. The data collection was done between 15 April to 07 May 2017. Results: The overall prevalence of dental caries in study population was 88.57%. The mean DMFT of all study participants was 17.13 (SD=10.48; participants were allocated a DMFT of 32). Majority of elder people (56.33%) had experience of pain and discomfort in their teeth within 12 months. The gender, marital status, diet, socio-economic status, medication, method of cleaning, frequency of cleaning, dental visit and tobacco chewing were factors that determines dental caries. Regular dental checkup (11%) was very poor. Majority of respondents preferred tea with sugar, biscuits/cake, chocolate and soft drinks (64%). Conclusions: The study showed that the prevalence of dental caries among elderly people in Rajdevi Rural Municipality, Rautahat District, Nepal was high. The awareness should be provided to local residents regarding the importance of good brushing habits and regular dental visits. Oral health policies are needed revised and implemented focusing on the special needs of this population to improve their quality of life.